Penciptaan Skenario Cahaya Hangat Di Kala Hujan untuk Menerapkan Teori Five Stages of Grief - Budiman, Muhammad Farrell (Cinelook: Journal of Film, Television, and New Media, 2024)
The screenplay for the film Cahaya Hangat Di Kala Hujan seeks to inform to readers the struggle of a cancer patient in healing himself physically and psychologically. So that readers can understand the importance of maintaining health. The screenplay for the film Cahaya Hangat Di Kala Hujan tells about the struggle of a woman with leukemia to maintain her life and her relationship with a man she meet at her new school.The creation of the screenplay for Cahaya Hangat Di Kala Hujan was inspired by the theory of the Five Stages of Grief, which involves the period of time during of which a person adjusts to the reality of their impending death or grief. There are Five Stages of Grief, including denial, anger, bargaining, depression, and acceptance. This is a method of assisting leukemia patients in resolving their issues.This work applies the theory of the Five Stages of Grief to the scenario Cahaya Hangat Di Kala Hujan by incorporating if with the three act narrative structure. The result of this work is every stage of sadness that the main female character goes through is reflected in the narrative structure, which also goes according to the character's emotional condition. It is might because the theory of the Five Stages of Grief has the same graph as the structure of three rounds, where the graph rises and reaches a climax.